The Value of the Samaritan Versions for the Textual History of the Samaritan Pentateuch - Schorch, Stefan 1966- (2021)
Abstract The Samaritan Aramaic Targum presents an extremely literal translation of SP , but the measure of literalness varies between different manuscripts. Further textual differences between these manuscripts can be related to different Hebrew Vorlagen, or to different interpretations of one and the same Hebrew Vorlage. It can thus be concluded that the Samaritan Targum tradition does not represent a single Aramaic translation of SP , but rather consists of several translations, based on different Hebrew Vorlagen. SAT and also the Samaritan Arabic translation are therefore important witnesses for the textual history of SP , relating to the written transmission of SP in the period before the 12th century CE , for which no Hebrew manuscripts are extant, and also to the Samaritan vocalization. This evidence demonstrates that the textual variety found in the Hebrew manuscripts of SP was already present in the transmission of SP between the 1st and the 11th century CE .
Keywords: Torah; Textual History; Hebrew Bible; Textual Criticism; Hebrew Bible; Samaritan Arabic translation; Samaritan Targum; Samaritan Pentateuch (SP)